Corporate social responsibility disclosures and corporate financial performance: evidence from OECD countries climate policy uncertainty - Anwer Hamad, Hawkar; Cek, Kemal; Abdullah, Hariem (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
This study aimed to investigate non-financial firms belonging to Organization for Economic Cooperation and Development (OECD) economies affected by climate policy uncertainty and corporate social responsibility disclosures in terms of their financial performance. To conduct this quantitative study, 625 non-financial firms across six OECD countries’ stock markets were selected for ten years (2012-2021). The research gathered data on CSR disclosures, financial performance, and climate policy uncertainty from a reliable database, DataStream, which examined research on OECD-listed firms. The study used a two-stage GMM to determine the relationship between CSR disclosures and corporate financial performance. The results showed that CSR disclosures, firm age, firm size, and gross domestic product were significant at the 1%, 5%, and 10% levels in explaining the relationship with corporate financial performance, which showed a negative relationship with corporate financial performance. Additionally, the research found that climate policy uncertainty was a key factor motivating CSR disclosure practices, ultimately improving corporate financial performance. This study has implications for researchers, investors, the government, and regulatory authorities.